Effect of Saline Water on Relative Water Content, Rate of Photosynthesis, Chlorophyll Content and Yield of Indian Mustard (brassica Juncea L.) - Shanker, Kripa; Parihar, S. K. S.; Biswas, S. K.; Kuldeep (International Journal of Bio-resource and Stress Management, 2014)
Effect of salinity on relative water content, rate of photosynthesis, total chlorophyll content and seed yield plant-1 of Indian mustard (viz., urvashi, Basanti, Varuna, Rohini and Ashirwad) of five genotypes showed increasing trend with 3 dS m-1 salinity over normal salinity in all characters, but further increase in salinity beyond 3 dS m-1 recorded significant reductions in all above mentioned crop characters up to highest salinity of 12 dS m-1. among genotypes, Urvashi registered significantly highest values of all crop parameters, while Ashirwad performed poorest in all cases. Thus, urvashi proved to be more salt tolerant than other genotypes, while Ashirwad proved to be most susceptible towards irrigation water salinity.